Social Interaction And Behavior In The Silent Patient Novel - Nirmala Sampe Ada; Dahlia D. Moelier; Andi Tenri Abeng (Fakultas Sastra, Universitas Bosowa, 2023)
This research discusses the types of social interaction and behaviour of the main character in a novel entitled The Silent Patient by Alex Michaelides which was published in 2019. This research used descriptive qualitative method and focuses on Sheickman's theory of social interaction: co-operation, accommodation, and assimilation and Skinner's theory of behaviour: neutral operant, reinforces and punishers. Furthermore, the data were analysed using a descriptive qualitative method. Writer use the novel as a valid data instrument. The result of this study in finding out that there are several types of social interaction resulting in the occurrence of both positive and negative interactions that occur in the novel, there are 15 data that divided into two parts namely social interaction and impact of responses and how social interaction can influence the formation or change of a behaviour, the result shows that the change of behaviour only appear in negative responses, and the punishers in the form of punishment for a person behaviour so that the behaviour or action does not happen again, this is how the behaviour can affect social interaction as depicted in the novel.